Efektivitas Penggunaan Flashcard Digital Untuk Meningkatkan kemampuan Kosakata Pada Anak Autisme Di Surakarta: THE EFFECTIVENESS OF USING DIGITAL FLASHCARDS TO IMPROVE VOCABULARY SKILLS IN CHILDREN WITH AUTISM IN SURAKARTA - Azizah, Mardhiatul; Putri, Anggi Resina; Setyaningsih, Wiwik (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Al Islam Bandung, 2025)
Vocabulary use is one of the important aspects of language development. In children, childhood is the optimal period for vocabulary development. Children with autism often experience language delays and have limited speaking abilities, which affects vocabulary development. The use of flashcards has been proven to help improve vocabulary skills. Digital flashcards that are attractively designed can provide visual and cognitive stimulation, effectively supporting language development, especially for children with autism. To determine the effectiveness of using digital flashcards to improve vocabulary skills in children with autism in Surakarta. This type of research is quantitative with a research design of pre-experimental design and using a group pretest-posttest design as a method of data collection approach. The sampling technique used was purposive sampling with a sample of 15 respondents. The statistical test used was the Wilcoxon test. The results of the Wilcoxon test obtained a sign.